The Role of Social Media on Subjective Well-Being of Adolescents: a Systematic Literature Review - Dewi, Ismira; Kasturi, Taufik; Purwandari, Eny (Universitas Ahmad Dahlan, 2024)
The rapidly increasing use of social media among adolescents has attracted much research interest in recent years. This scoping review was conducted to examine the effects of social media on adolescents' subjective well-being, including the possible elements of positive effects, negative effects, and life satisfaction. The methodology used in this scoping review included gathering research articles from various databases from Publish or Perish and Scopus, spanning the years 2018 to 2023. After reviewing the selected 10 articles, it was found that seven of them supported the existing connection between social media use and adolescents' subjective well-being. On the contrary, three articles suggested no significant influence between social media and adolescents' subjective well-being.